2004
DOI: 10.1613/jair.1492
|View full text |Cite
|
Sign up to set email alerts
|

Ordered Landmarks in Planning

Abstract: Many known planning tasks have inherent constraints concerning the best order in which to achieve the goals. A number of research efforts have been made to detect such constraints and to use them for guiding search, in the hope of speeding up the planning process. We go beyond the previous approaches by considering ordering constraints not only over the (top-level) goals, but also over the sub-goals that will necessarily arise during planning. Landmarks are facts that must be true at some point in every va… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
251
0
10

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(261 citation statements)
references
References 20 publications
0
251
0
10
Order By: Relevance
“…The first one is the conception of heuristic functions to guide search algorithms (Richter, Helmert & Westphal, 2008;Richter & Westphal, 2010;Helmert & Domshlak, 2009). Another use of landmarks is to partition the problem into easier subproblems whose goals are disjunctions of landmarks (Hoffmann, Porteous & Sebastia, 2004;Sebastia, Onaindia & Marzal, 2006). More recently, Vernhes, Infantes and Vidal (2013) define a landmark-based meta best-first search algorithm.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The first one is the conception of heuristic functions to guide search algorithms (Richter, Helmert & Westphal, 2008;Richter & Westphal, 2010;Helmert & Domshlak, 2009). Another use of landmarks is to partition the problem into easier subproblems whose goals are disjunctions of landmarks (Hoffmann, Porteous & Sebastia, 2004;Sebastia, Onaindia & Marzal, 2006). More recently, Vernhes, Infantes and Vidal (2013) define a landmark-based meta best-first search algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…However, some landmarks can be found more efficiently by using various techniques: Porteous and Cresswell (2002) and Hoffmann, Porteous and Sebastia (2004) present methods for detecting landmarks and relations between landmarks based on backchaining from the goals in the relaxed planning graph, whereas Zhu and Givan (2003) use forward propagation in the same graph and Richter, Helmert and Westphal (2008) use the domain transition graph, a graph whose nodes represent the possible values of the variable and edges represent the possible transitions between values induced by actions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The idea to divide the plan trajectory into small chunks has been studied with success in [11]. The authors have shown the existence of landmarks 4 and the impact of ordering them on search efficiency.…”
Section: Introductionmentioning
confidence: 99%